Synergistic antimicrobial activity of oregano and thyme thymol essential oils against Leuconostoc citreum in a laboratory medium and tomato juice. (September 2020) - Lee, Sohyun; Kim, Hoikyung; Beuchat, Larry R.; Kim, Yoonsook; Ryu, Jee-Hoon
Abstract: This study was done to identify combinations of essential oils (EOs) that elicit synergistic antimicrobial effects against Leuconostoc citreum, a spoilage bacterium in vegetable and fruit juices. Twenty-four EOs were tested for antimicrobial activity against L. citreum using an agar well diffusion assay. Ten EOs showed relatively strong antimicrobial activity. Among those, cinnamon bark, oregano, and thyme thymol EOs showed the strongest activity (minimal inhibitory concentration = 1.25 μL/mL). It was confirmed that a combination of oregano and thyme thymol EOs had a synergistic antimicrobial activity (fractional inhibitory concentration index = 0.3750) using a checkerboard assay. This combination also had a synergistic antimicrobial activity against L. citreum in tomato juice. An initial population of L. citreum in tomato juice (5.3 log CFU/mL) increased to ≥ 8.6 log CFU/mL within 48 h at 15 °C and 24 h at 25 °C. Populations reached 6.8–7.2 log CFU/mL in tomato juice containing either 0.156 mL/mL oregano or thyme thymol. However, in the presence of both EOs (0.156 μL/mL in total), populations of L. citreum were significantly lower (5.7–6.5 log CFU/mL) ( P ≤ 0.05). Findings will be useful when developing non-thermal food preservation technologies to increase the shelf-life of juices and other foods not containing synthetic preservatives. Highlights: Essential oils (EOs) with synergistic lethal effects against L. citreum was identified. Cinnamon bark, oregano, and thyme thymol EOs showed the lowest MIC in a medium. Oregano and thyme thymol EOs showed a synergy in inhibiting L. citreum in a medium. This combination showed a synergistic inhibition against L. citreum in tomato juice.